Recent trends in life expectancy across high income countries: retrospective observational study. (15th August 2018) - Ho, Jessica Y; Hendi, Arun S
Abstract: Objectives: To assess whether declines in life expectancy occurred across high income countries during 2014-16, to identify the causes of death contributing to these declines, and to examine the extent to which these declines were driven by shared or differing factors across countries. Design: Demographic analysis using aggregated data. Setting: Vital statistics systems of 18 member countries of the Organisation for Economic Co-operation and Development. Participants: 18 countries with high quality all cause and cause specific mortality data available in 2014-16. Main outcome measures: Life expectancy at birth, 0-65 years, and 65 or more years and cause of death contributions to changes in life expectancy at birth. Results: The majority of high income countries in the study experienced declines in life expectancy during 2014-15; of the 18 countries, 12 experienced declines in life expectancy among women and 11 experienced declines in life expectancy among men. The average decline was 0.21 years for women and 0.18 years for men. In most countries experiencing declines in life expectancy, these declines were predominantly driven by trends in older age (≥65 years) mortality and in deaths related to respiratory disease, cardiovascular disease, nervous system disease, and mental disorders. In the United States, declines in life expectancy were more concentrated at younger ages (0-65 years), and drug overdose and other external causes of death played important roles in driving these declines. Conclusions: Most of the countries that experienced declines in life expectancy during 2014-15 experienced robust gains in life expectancy during 2015-16 that more than compensated for the declines. However, the United Kingdom and the United States appear to be experiencing stagnating or continued declines in life expectancy, raising questions about future trends in these countries.